The Effectiveness of Entrepreneurial Education Programs in Kenya - Chege Salem Kabue (International Journal of Science and Society, 2022)
There has been a shift toward placing an excessive amount of focus on financial, legal, and regulatory factors, as well as environmental variables, in entrepreneurship courses. The research team in this study set out to answer the question, "How does entrepreneurship training affect business performance in Bungoma County?" Because of its extreme poverty and high unemployment rate, Bungoma County was named a Millennium District in 2006. Stakeholders' attempts to boost entrepreneurs' capacity through a range of training programs have been attributed to a lack of entrepreneurial culture and entrepreneurial abilities among the indigenous people, who face the twin issues of extreme poverty and unemployment. To what extent these trainings impacted business performance was the focus of this research. This research built on Kirkpatrick's (2003) revised model for program evaluation and planning in training. The data from the study were analyzed using a correlational technique. Based on the results of the research, it is clear that the trainings did not significantly improve participants' MSE scores. There was no clear progression from micro to small to medium to large firms across the enterprise continuum, highlighting the need for enhancement to meet the specific needs of entrepreneurs and small business owners. There has to be a standardized method for the government and enterprise development agents to assess the effectiveness of training and make adjustments for the betterment of the sector.